Acetylcholine receptors of the neuromuscular junctions present normal distribution after peripheral nerve injury and repair through nerve guidance associated with fibrin biopolymer - Leite, Ana Paula Silveira [UNESP]; Pinto, Carina Guidi [UNESP]; Tibúrcio, Felipe Cantore [UNESP]; Muller, Kevin Silva [UNESP]; Padovani, Carlos Roberto [UNESP]; Barraviera, Benedito [UNESP]; Junior, Rui Seabra Ferreira [UNESP]; Leal, Claudenete Vieira; Matsumura, Cintia Yuri [UNESP]; Matheus, Selma Maria Michelin [UNESP] (Elsevier, 2023)
Peripheral nerve injuries (PNI) lead to alterations in the Agrin-LRP4-MuSK pathway. This results in disaggregation of AChRs and change from epsilon (mature, innervated) to gamma (immature, denervated) subunit. Tubulization technique has been shown to be effective for PNI repair and it also allows the use of adjuvants, such as fibrin biopolymer (FB). This study evaluated the effect of the association of tubulization with FB after PNI on AChRs and associated proteins. Fifty-two adults male Wistar rats were used, distributed in 4 experimental groups: Sham Control (S), Denervated Control (D); Tubulization (TB) and Tubulization + Fibrin Biopolymer (TB+FB). Catwalk was performed every 15 days. Ninety days after surgery the right soleus muscles and ischiatic nerves were submitted to the following analyses: (a) morphological and morphometric analysis of AChRs by confocal microscopy; (b) morphological and morphometric analysis of the ischiatic nerve; (c) protein quantification of AChRs: alpha, gama, and epsilon, of Schwann cells, agrin, LRP4, MuSK, rapsyn, MMP3, MyoD, myogenin, MURF1 and atrogin-1. The main results were about the NMJs that in the TB+FB group presented morphological and morphometric approximation (compactness index; area of the AChRs and motor plate) to the S group. In addition, there were also an increase of S100 and AChRε protein expression and a decrease of MyoD. These positive association resulted in AChRs stabilization that potentiate the neuromuscular regeneration, which strengthens the use of TB for severe injuries repair and the beneficial effect of FB, along with tubulization technique.
Keywords: Acetylcholine receptors; Fibrin biopolymer; Neuromuscular junction; Peripheral nerve injury; Polycaprolactone